Influenza surveillance in 15 countries in Africa, 2006-2010. - (:unkn) unknown (My University, 2012)
BACKGROUND: In response to the potential threat of an influenza pandemic, several international institutions and governments, in partnership with African countries, invested in the development of epidemiologic and laboratory influenza surveillance capacity in Africa and the African Network of Influenza Surveillance and Epidemiology (ANISE) was formed. METHODS: We used a standardized form to collect information on influenza surveillance system characteristics, the number and percent of influenza-positive patients with influenza-like illness (ILI), or severe acute respiratory infection (SARI) and virologic data from countries participating in ANISE. RESULTS: Between 2006 and 2010, the number of ILI and SARI sites in 15 African countries increased from 21 to 127 and from 2 to 98, respectively. Children 0-4 years accounted for 48% of all ILI and SARI cases of which 22% and 10%, respectively, were positive for influenza. Influenza peaks were generally discernible in North and South Africa. Substantial cocirculation of influenza A and B occurred most years. CONCLUSIONS: Influenza is a major cause of respiratory illness in Africa, especially in children. Further strengthening influenza surveillance, along with conducting special studies on influenza burden, cost of illness, and role of other respiratory pathogens will help detect novel influenza viruses and inform and develop targeted influenza prevention policy decisions in the region.
Keywords: African Research